Combined visual and dribbling performance in young soccer players of different expertise - Bekris, E.; Gissis, I.; Ispyrlidis, I.; Mylonis, E.; Axeti, G. (Research in Sports Medicine, 2018)
We aimed to evaluate dribbling performance in terms of technique and visual skills assessment of both young experienced (EX, n = 24) and novice (NO, n = 24) soccer players. Both groups performed two dribbling tests with four levels of difficulty in visual signals (A1-A4 and B1-B4; B - half distance of A; 1 - no visual signal; 4 - signal with the shorter flashing time). All players performed slower when visual signals were added to the testing process (~2.5 s; p < 0.01). EX completed all tests faster than NO (~3 s, p < 0.01). The average number of visual mistakes was significantly lower for EX than NO in all tests (p < 0.01). These results demonstrated the importance of evaluating dribbling along with visual stimuli in young soccer EX and NO players.